2008
DOI: 10.1097/mat.0b013e3181744071
|View full text |Cite
|
Sign up to set email alerts
|

A Performance Evaluation of Eight Geometrically Different 10 Fr Pediatric Arterial Cannulae Under Pulsatile and Nonpulsatile Perfusion Conditions in an Infant Cardiopulmonary Bypass Model

Abstract: This investigation compared pressure drops and surplus hemodynamic energy (SHE) levels in eight commercially available pediatric aortic cannulae (10 Fr) with different geometries during pulsatile and nonpulsatile perfusion conditions in an in vitro infant model of cardiopulmonary bypass. For each trial, the cannula was placed at the distal end of the arterial line, and the insertion tip was fixed to the inlet of the simulated patient. The pseudo patient was subjected to seven pump flow rates ranging from 400 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…TCD was used to record cerebral blood flow waveforms generated by pulsatile and nonpulsatile flow settings, which were analyzed computationally to yield Gosling's PI values for subsequent statistical analysis. Previous research has shown the challenges of generating pulsatile flow with small diameter aortic cannulae (16); PI data presented below enables quantitative assessment of the quality of pulsatile perfusion attained.…”
Section: Resultsmentioning
confidence: 99%
“…TCD was used to record cerebral blood flow waveforms generated by pulsatile and nonpulsatile flow settings, which were analyzed computationally to yield Gosling's PI values for subsequent statistical analysis. Previous research has shown the challenges of generating pulsatile flow with small diameter aortic cannulae (16); PI data presented below enables quantitative assessment of the quality of pulsatile perfusion attained.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, an aortic cannula that produces favorable results in terms of pressure drops and delivery of pulsatile energy must be carefully chosen to achieve physiologic pulsatile flow. 13 Even when a proper circuit is chosen, it is inevitable that most of the hemodynamic energy is damped by the circuit. In this study, we focused on the actual amount of hemodynamic energy delivered to end organ vessels in an in vivo model.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators have been using different extracorporeal circuits including different oxygenators, filters, venous and arterial cannulas, and coating material. [12][13][14][15] The use of suboptimal extracorporeal circuits has confused results as well. Most of the hemodynamic energy is lost by extracorporeal circuit components, including the hollow fiber membrane oxygenator, arterial filter, arterial cannula, purge line of the arterial filter, and the length of the arterial tubing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, cannulae have been studied experimentally, to determine pressure drops and hemodynamic energy 21 and in vivo , to investigate biocompatibility and blood damage 12,13. There have also been several numerical studies: parameterized models have been used to investigate the influence of side holes on peak shear rates and flow distribution 22,23; models of specific hemodialysis cannulae have been used to validate hemolysis calculations 24 and study flow fields in a more complicated cannula design 25; a study on a new design for a cardiopulmonary bypass cannula predicted higher flow rates and exit velocities compared with a control cannula 26; and, in a new design for an artificial lung access cannula 27, the influence of the novel geometry on shear stress distribution and hemolysis production was assessed 28.…”
Section: Introductionmentioning
confidence: 99%